Negara Dan Golkar (Studi Tentang Konfigurasi Politik Tahun 1971-2009) - Gatot Sudjito (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
The study aims to answer the question of how: (1) political configuration that puts Indonesia in 1971-1997 Golkar as a single force (2) political configuration in 1998 that caused the New Order government fell, and (3) the political configuration in 1999-2009 resulting Golkar political disorientation.The results: (1) the political configuration of Indonesia in 1971-1997 accidentally put Golkar as a single force on the grounds that the government can carry out the construction with smooth and stable. Sekber-military form with the government, Golkar then follow the 1971 general election and won an absolute acquire 62.82% of the vote. Thanks to that victory, Golkar and the military dominated parliament. Various attempts were made by the government in order to Golkar remains a singular force that harm the PPP and PDI, the result, until the 1997 election Golkar always wins absolute; (2) As a result of the New Order regime always manipulate the order absolute win Golkar, the public is not satisfied, the scent of corruption in the preparation of Development Cabinet VII concurrent multi-dimensional crisis of 1997 to encourage people demanded a change in many lives. The insistence of the President submit his cause to BJ Habibie to date. May 21, 1998. Since then New Order, (3) After the fall of the New Order, Golkar as also fell. With the remnants of the existing resources can Golkar following the 1999 elections, the results dropped dramatically compared to the 1997 election due to: (1) Chairman of the Board of Trustees of the New Order era Golkar political structure intact bequeath to future generations, (2) the Golkar elite divisions; (3) the loss of support of the military and civil servants, (4) a more competitive electoral policies, (5) the division of voters into 47 political parties, (6) the emergence of a new reformist parties. The success of the Golkar Party in the 2004 elections resulting from the internal side: (1) the Golkar Party fought a modern and independent party, (2) political machine that has formed revived; (3) more democratic, (4) the persistence of traditional voters, and (5 ) personal factors Akbar. Of external factors as: (1) some people miss the New Order government and re-select the Golkar Party, (2) Some supporters of the PDI-P in the 1999 elections Golkar.Faktor Party switched its support to the cause of decreased Golkar election ballot back in 2009 from an internal include: (1) culture convention in the selection of candidates for President are not followed, the image of Golkar party as the party of democratic aspirations in a leadership cadre that has been built to fade back, (2) is controlled by Golkar non reformist leadership, encouraging party elite oligarchic; (3) efforts build the party into a modern party that has been initiated prior periods become dormant due to the busy Chairman stints as Vice President. On the external side: (1) magnetic figure Susilo Bambang Yodoyono lead Golkar voters switched its support to the Democrats in the 2009 election, and (2) The release of some of the Golkar Party elite.Keywords: State, Golkar, Political Configuration.